Alphabet Energy - Alexander, Beverly; Boscoe, Adam; Cabot, Mason; Dawsey, Philip; Barreau, Luc Emmanuel; Griffith, Russel (London : SAGE Publications Ltd, 2017)
Alphabet Energy was founded in 2009 with a new thermoelectric technology that had the potential to advance energy efficiency by recovering heat wasted in combustion and mechanical processes. Matt Scullin, Alphabets founder, and his team were convinced that their product was cheaper to produce, and therefore had more than 80 different potential applications. By 2010, Alphabet was facing its biggest challenge yet how to select its initial market. After receiving seed funding in early 2010, Alphabet was choosing among four markets: Automotive, Aerospace and Defense, Power Generation, and Manufacturing. Students are provided information to help them make a recommendation.
Originally published: Alexander, B., Boscoe, A., Cabot, M., Dawsey, P., Barreau, L. E., & Griffith, R. (2014). Alphabet Energy. The Berkeley-Haas Case Series. University of California, Berkeley. Haas School of Business.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Alphabet Energy; Business planning; Strategic planning; Energy consumption